PPAT'S Legal Responsibility For The Creation Of Empty Deed - Wirantia Wirantia; Darmawan Darmawan; Suhaimi Suhaimi (Syiah Kuala Law Journal, 2020)
Article 53 of the Regulation of the Head of the National Land Agency Number 1 Year 1960, which states that the PPAT deed is made by filling in the complete available deed blanks in accordance with the instructions for filling it. In practice carried out by a small number of PPAT there is a deed that has been prepared in advance, and has had some contents emptied containing agreements or general and standard agreements, which the purpose of which is to facilitate the work of PPAT in terms of administration and in terms of providing services by PPAT to interested parties or faces. The results showed that, Responsibility for authentic deed which is partially subtansinya empty, because PPAT is a public official who is given the authority to make authentic deed and PPAT has rules that must be obeyed by all PPAT in Indonesia regulated in Government Regulation No. 24, 2016 and the IPPAT Code of Ethics, and the position of PPAT deed which is partially subtansinya vacant in the event of degradation of PPAT deed even though the PPAT deed is a perfect evidence tool, but in the ppat certificate can experience degradation of the deed that can not be enforced as an authentic deed, but is considered a deed / handwriting under the hands caused by violation of the provisions of Article 1869 KUHPerdata.